Edukasi Kesehatan Tentang Terapi Foot Massage untuk Penurunan Tekanan Darah di Desa Klieng Cot Aron - Ellyza Fazlylawati; Muhammad Reza Rizki; Nurul Amna (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Hypertension is a chronic condition characterized by blood pressure exceeding the normal range, specifically 140/90 mmHg. One of the primary contributors to hypertension is insufficient potassium intake. Studies suggest that foods rich in potassium, such as pumpkin, can help regulate blood pressure. Pumpkin is an excellent source of potassium and dietary fiber, which are beneficial in managing hypertension. This health education program aimed to provide the Cot Paya community with knowledge about how pumpkin pudding can be used as a natural remedy to lower blood pressure. The method employed in this activity included a lecture followed by a question-and-answer session, allowing for an interactive exchange of information. The intervention focused on educating families and elderly individuals about the causes of hypertension, its impact on health, and the potential benefits of incorporating pumpkin pudding into their diet. The response from the Cot Paya community was positive, with many participants showing keen interest in the topic. Several parents and elderly residents actively engaged by asking questions related to hypertension and its management. The educational session not only improved awareness about hypertension but also provided practical knowledge on using pumpkin pudding as a dietary tool for managing high blood pressure. By the end of the session, participants demonstrated a better understanding of hypertension, its prevention, and the role of potassium-rich foods like pumpkin in reducing blood pressure. The activity was well-received and laid the foundation for continued health education within the community, particularly in promoting natural dietary interventions to prevent and manage hypertension.